High-temperature-resistant wave-absorbing composite rubber material and preparation method thereof
By using a combination of alumina fibers, KH550, gel, suspension, carbonyl iron powder and dimethyl silicone oil in the absorbing material, the problem of performance attenuation of absorbing materials under high temperature conditions is solved, and the high temperature stability of the material is achieved Improved performance and absorbing performance, suitable for complex working environments.
Patent Information
- Application Number
- CN202411305264.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
AI Technical Summary
Existing absorbing materials are prone to attenuation of absorbing properties and decreased mechanical strength under high temperature conditions, poor compatibility between fillers and substrates, resulting in deterioration of material properties. The traditional preparation process is complex and costly, making it difficult to meet large-scale production and practical applications. need.
By combining components such as alumina fibers, KH550, gels, suspensions, carbonyl iron powder and dimethyl silicone oil to form high-temperature absorption composite materials, preventing phase separation through molecular and physical actions, and enhancing the material's Stability and absorbency.
Maintain good stability and wave absorption effect of the material under high temperature conditions, ensure that the material continues to perform good performance in complex environments, and improve the material's heat resistance, wave absorption and mechanical properties.
Smart Images

Figure BDA0005048974300000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer composite material preparation, and relates to a high temperature resistant wave absorbing composite rubber material and a preparation method thereof. Background Art
[0002] In today's era of rapid development of high technology, the widespread use of electromagnetic waves has brought about serious electromagnetic pollution and electromagnetic interference problems. As a key means to solve this problem, the performance of absorbing materials directly affects the normal operation and reliability of related equipment. In the fields of aerospace, 5G communications, automotive electronics, etc., materials often need to maintain stable performance in high temperature environments, which places extremely high demands on the high temperature resistance of absorbing materials.
[0003] Existing absorbing materials often have difficulty in taking into account mechanical properties, high temperature resistance and absorbing performance when dealing with complex and changeable working environments. For example, common absorbing materials are prone to attenuation of absorbing performance and decrease in mechanical strength under high temperature conditions; poor compatibility between fillers and matrix leads to uneven dispersion, which seriously affects the overall performance of the material. In addition, the traditional preparation process is complex and costly, making it difficult to meet the needs of large-scale production and practical applications. Summary of the invention
[0004] The object of the present invention is to provide a high temperature resistant wave absorbing composite rubber material and a preparation method thereof. The present invention cooperates with components such as gel, suspension, carbonyl iron powder and dimethyl silicone oil to effectively prevent phase separation through molecular and physical effects, thereby avoiding structural defects and performance degradation inside the material. This synergistic effect enables the material to maintain good stability and wave absorbing effect under high temperature conditions, ensuring that the material can continue to perform well in a complex working environment.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a high temperature resistant wave absorbing composite rubber material, the preparation method comprising the following steps:
[0007] (1) Alumina fiber and KH550 are mixed, stirred in a high-speed stirrer to obtain surface-treated alumina fiber, and then ethyl orthosilicate, ethanol solution and deionized water are added, stirred at room temperature for 4-8 hours to form a sol, aged, and obtained a gel;
[0008] (2) performing surface modification treatment on the filler to obtain a modified filler, and then mixing the modified filler with N-isopropyl-N'-phenyl-p-phenylenediamine and a softener and then ball milling to obtain a ball milling product;
[0009] (3) mixing the ball-milled product, acetone, and polyvinyl pyrrolidone, and performing ultrasonic dispersion to obtain a suspension;
[0010] (4) mixing the gel, the suspension, the carbonyl iron powder, and the dimethyl silicone oil, and stirring the mixture in a high-speed stirrer to obtain a mixed slurry;
[0011] (5) After the mixed slurry is degassed, it is filled to obtain a high temperature resistant and wave absorbing composite rubber material.
[0012] Furthermore, the mass ratio of alumina fiber to KH550 in step (1) is 4.21-5.45:0.8-1.2; the parameters of the high-speed stirrer in step (1) are: stirring speed is 1000-1500rmp, stirring time is 10-20min; the mass ratio of surface-treated alumina fiber, tetraethyl orthosilicate, ethanol solution and deionized water in step (1) is 3.72-5:0.64-1:2.8-4:8-12; the mass concentration of the ethanol solution is 50-70wt%; the parameters of the aging step in step (1) are: aging temperature is 50-70°C, and aging time is 12-24h.
[0013] Furthermore, the filler in step (2) is selected from one or more of silicon dioxide, bentonite and diatomaceous earth; the mass ratio of the modified filler, N-isopropyl-N'-phenyl-p-phenylenediamine and the softener in step (2) is 4.7-6.3:0.6-0.88:0.8-1.2; the softener is selected from one of aromatic oil, cycloalkane oil and paraffin oil; the parameters of the ball milling step in step (2) are: the ball milling speed is 300-700rmp, and the ball milling time is 2-4h.
[0014] Furthermore, the preparation method of the modified filler is:
[0015] The filler and methanol are mixed, and the ultrasonic temperature is set to 35-55°C. After ultrasonic treatment for 10-20 minutes, a suspension is obtained, γ-mercaptopropyltrimethoxysilane, styrene, and potassium persulfate are added, and the mixture is stirred at 45-55°C for 1-3 hours to obtain a mixture, and then p-hydroxyanisole and diethylenetriamine are added, and 1-3wt% acetic acid solution is added dropwise, and the mixture is stirred at 70-80°C for 2-3 hours. The mixture is filtered through a 200-mesh filter cloth, and the obtained precipitate is washed with deionized water and dried to obtain a modified filler.
[0016] Furthermore, the mass ratio of the filler to methanol is 3.7-5.5:14-18; the mass ratio of the suspension, γ-mercaptopropyltrimethoxysilane, styrene and potassium persulfate is 5.45-7:0.72-1.12:0.9-1.2:0.03-0.07; the mass ratio of the mixture, p-hydroxyanisole, diethylenetriamine and 1-3wt% acetic acid solution is 4.5-6:0.52-0.78:0.61-0.93:0.05-0.15.
[0017] Furthermore, the mass ratio of the ball milling product, acetone and polyvinyl pyrrolidone in the step (3) is 5.1-5.5:7-10:0.9-1.3; the parameters of the ultrasonic step in the step (3) are: ultrasonic power of 200-400W, ultrasonic frequency of 30-40kHz, ultrasonic temperature of 40-60°C, and ultrasonic time of 20-40min.
[0018] Furthermore, the mass ratio of the gel, suspension, carbonyl iron powder and dimethyl silicone oil in step (4) is 2.35-3.05:3.4-4.5:20-50:45-89; the parameters of the high-speed stirrer in step (4) are: stirring speed is 1500-2000rmp, and stirring time is 1-3h.
[0019] Furthermore, the degassing time in step (5) is 1-2 hours.
[0020] Beneficial effects of the present invention:
[0021] (1) After the alumina fiber of the present invention is treated with KH550, the surface active groups increase significantly. These active groups react with the silanol groups produced by the hydrolysis of ethyl orthosilicate to form a stable silicon-oxygen bond network on the fiber surface, effectively enhancing the interfacial bonding between the fiber and the matrix material, so that the fiber can be more firmly bonded to the matrix material. In addition, the alumina fiber acts as a strong reinforcing skeleton in the matrix due to its high strength and high heat resistance. This skeleton effectively improves the mechanical strength of the material. Through gel treatment and subsequent blending, the alumina fiber is evenly dispersed in the entire system, especially in a high temperature environment, which can prevent the material from being deformed and damaged due to heat, greatly improving the heat resistance of the material.
[0022] (2) The present invention performs double modification on the filler. The trimethoxysilane group in γ-mercaptopropyltrimethoxysilane interacts with the active group on the surface of the filler, and then introduces carbon-carbon double bonds with the help of styrene to interact with other active molecules, thereby changing the chain structure and spatial arrangement of the molecule, increasing the interfacial bonding force between the filler and the matrix material, and improving the compatibility and dispersibility of the filler in the entire system. By adding hydroxyanisole and diethylenetriamine, the aldehyde group or ketone group reacts with the amino group through a nucleophilic addition reaction, and then eliminates a molecule of water to form a Schiff base structure with an imine bond (C=N). The Schiff base structure has excellent thermal stability and can withstand high temperatures without significant decomposition or structural changes, thereby effectively improving the high temperature resistance of the material. In addition, the filler after double modification forms numerous tiny and uniform microscopic interfaces. Under the action of electromagnetic waves, these microscopic interfaces can cause multiple reflections, refractions and scattering of electromagnetic waves, thereby increasing the propagation path and energy loss of electromagnetic waves inside the material. The interaction between the electromagnetic waves and the functional groups on the surface of the filler and the matrix molecules further promotes the absorption and conversion of the electromagnetic waves, thereby significantly improving the wave absorption performance of the material.
[0023] (3) The present invention also adds carbonyl iron powder and dimethyl silicone oil. The carbonyl iron powder has high magnetic permeability and good wave absorbing performance. By interacting with the modified alumina fibers and the active groups on the surface of the filler, the carbonyl iron powder can be dispersed more evenly in the gel to avoid agglomeration. The evenly dispersed carbonyl iron powder can form a continuous wave absorbing network in the gel, thereby improving the wave absorbing performance of the material. The fluidity of dimethyl silicone oil allows it to penetrate into the stacking gaps between the carbonyl iron powder particles and other filling materials, which can effectively exclude air, improve the density and structural stability of the material, reduce the dielectric constant and magnetic permeability of the material, and thus improve the wave absorbing performance of the material. In addition, the increase in material density can better withstand external forces and thermal stresses, improve the overall mechanical properties of the composite rubber, and make the material less likely to crack or break when subjected to external mechanical effects.
[0024] (4) The present invention cooperates with the components such as gel, suspension, carbonyl iron powder and dimethyl silicone oil to effectively prevent phase separation through molecular and physical effects, thereby avoiding structural defects and performance degradation inside the material. This synergistic effect enables the material to maintain good stability and wave absorption effect under high temperature conditions, ensuring that the material can continue to perform well in a complex working environment. DETAILED DESCRIPTION
[0025] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0026] Example 1
[0027] A method for preparing a high temperature resistant wave absorbing composite rubber material, the preparation method of this embodiment comprises the following steps:
[0028] (1) Alumina fiber and KH550 are mixed and stirred in a high-speed stirrer to obtain surface-treated alumina fiber, and then ethyl orthosilicate, ethanol solution and deionized water are added, stirred at room temperature for 4 hours to form a sol, and aged to obtain a gel;
[0029] (2) performing surface modification treatment on the filler to obtain a modified filler, and then mixing the modified filler with N-isopropyl-N'-phenyl-p-phenylenediamine and a softener and then ball milling to obtain a ball milling product;
[0030] (3) mixing the ball-milled product, acetone, and polyvinyl pyrrolidone, and performing ultrasonic dispersion to obtain a suspension;
[0031] (4) mixing the gel, the suspension, the carbonyl iron powder, and the dimethyl silicone oil, and stirring the mixture in a high-speed stirrer to obtain a mixed slurry;
[0032] (5) After the mixed slurry is degassed, it is filled to obtain a high temperature resistant and wave absorbing composite rubber material.
[0033] The mass ratio of alumina fiber and KH550 in step (1) of this embodiment is 4.21:0.8; the parameters of the high-speed stirrer in step (1) of this embodiment are: stirring speed is 1000rmp, stirring time is 10min; the mass ratio of surface-treated alumina fiber, tetraethyl orthosilicate, ethanol solution and deionized water in step (1) of this embodiment is 3.72:0.64:2.8:8; the mass concentration of the ethanol solution in this embodiment is 50wt%; the parameters of the aging step in step (1) of this embodiment are: aging temperature is 50°C, aging time is 12h.
[0034] The filler in step (2) of this embodiment is silicon dioxide; the mass ratio of the modified filler, N-isopropyl-N'-phenyl-p-phenylenediamine and the softener in step (2) of this embodiment is 4.7:0.6:0.8; the softener in this embodiment is cyclohexane oil; the parameters of the ball milling step in step (2) of this embodiment are: the ball milling speed is 300 rpm and the ball milling time is 2 hours.
[0035] The preparation method of the modified filler of this embodiment is:
[0036] The filler and methanol were mixed, and the ultrasonic temperature was set to 35°C. After ultrasonic treatment for 10 minutes, a suspension was obtained. γ-mercaptopropyltrimethoxysilane, styrene, and potassium persulfate were added, and the mixture was stirred at 45°C for 1 hour. Then, p-hydroxyanisole and diethylenetriamine were added, and 1wt% acetic acid solution was added dropwise. The mixture was stirred at 70°C for 2 hours, and filtered through a 200-mesh filter cloth. The obtained precipitate was washed with deionized water and dried to obtain a modified filler.
[0037] The mass ratio of the filler and methanol in this embodiment is 3.7:14; the mass ratio of the suspension, γ-mercaptopropyltrimethoxysilane, styrene and potassium persulfate in this embodiment is 5.45:0.72:0.9:0.03; the mass ratio of the mixture, p-hydroxyanisole, diethylenetriamine and 1-3wt% acetic acid solution in this embodiment is 4.5:0.52:0.61:0.05.
[0038] The mass ratio of the ball-milled product, acetone and polyvinyl pyrrolidone in step (3) of this embodiment is 5.1:7:0.9; the parameters of the ultrasonic step in step (3) of this embodiment are: ultrasonic power of 200 W, ultrasonic frequency of 30 kHz, ultrasonic temperature of 40° C., and ultrasonic time of 20 min.
[0039] The mass ratio of the gel, suspension, carbonyl iron powder and dimethyl silicone oil in step (4) of this embodiment is 2.35:3.4:20:45, and the viscosity of the dimethyl silicone oil in this embodiment is 1000 mPa·s; the parameters of the high-speed stirrer in step (4) of this embodiment are: stirring speed is 1500 rpm, and stirring time is 1 hour.
[0040] The degassing time in step (5) of this embodiment is 1 hour.
[0041] Example 2
[0042] A method for preparing a high temperature resistant wave absorbing composite rubber material, the preparation method of this embodiment comprises the following steps:
[0043] (1) Alumina fiber and KH550 are mixed, stirred in a high-speed stirrer to obtain surface-treated alumina fiber, and then ethyl orthosilicate, ethanol solution and deionized water are added, stirred at room temperature for 8 hours to form a sol, aged, and obtained a gel;
[0044] (2) performing surface modification treatment on the filler to obtain a modified filler, and then mixing the modified filler with N-isopropyl-N'-phenyl-p-phenylenediamine and a softener and then ball milling to obtain a ball milling product;
[0045] (3) mixing the ball-milled product, acetone, and polyvinyl pyrrolidone, and performing ultrasonic dispersion to obtain a suspension;
[0046] (4) mixing the gel, the suspension, the carbonyl iron powder, and the dimethyl silicone oil, and stirring the mixture in a high-speed stirrer to obtain a mixed slurry;
[0047] (5) After the mixed slurry is degassed, it is filled to obtain a high temperature resistant and wave absorbing composite rubber material.
[0048] The mass ratio of alumina fiber and KH550 in step (1) of this embodiment is 5.45:1.2; the parameters of the high-speed stirrer in step (1) of this embodiment are: stirring speed is 1500rmp, stirring time is 20min; the mass ratio of surface-treated alumina fiber, tetraethyl orthosilicate, ethanol solution and deionized water in step (1) of this embodiment is 5:1:4:12; the mass concentration of the ethanol solution in this embodiment is 70wt%; the parameters of the aging step in step (1) of this embodiment are: aging temperature is 70°C, aging time is 24h.
[0049] The filler in step (2) of this embodiment is silicon dioxide; the mass ratio of the modified filler, N-isopropyl-N'-phenyl-p-phenylenediamine and the softener in step (2) of this embodiment is 6.3:0.88:1.2; the softener in this embodiment is cyclohexane oil; the parameters of the ball milling step in step (2) of this embodiment are: the ball milling speed is 700 rpm and the ball milling time is 4 hours.
[0050] The preparation method of the modified filler of this embodiment is:
[0051] The filler and methanol were mixed, and the ultrasonic temperature was set to 55°C. After ultrasonic treatment for 20 minutes, a suspension was obtained. γ-mercaptopropyltrimethoxysilane, styrene, and potassium persulfate were added, and the mixture was stirred at 55°C for 3 hours. Then, p-hydroxyanisole and diethylenetriamine were added, and 3wt% acetic acid solution was added dropwise. The mixture was stirred at 80°C for 3 hours, and filtered through a 200-mesh filter cloth. The obtained precipitate was washed with deionized water and dried to obtain a modified filler.
[0052] The mass ratio of the filler and methanol in this embodiment is 5.5:18; the mass ratio of the suspension, γ-mercaptopropyltrimethoxysilane, styrene and potassium persulfate in this embodiment is 7:1.12:1.2:0.07; the mass ratio of the mixture, p-hydroxyanisole, diethylenetriamine and 1-3wt% acetic acid solution in this embodiment is 6:0.78:0.93:0.15.
[0053] The mass ratio of the ball-milled product, acetone and polyvinyl pyrrolidone in step (3) of this embodiment is 5.5:10:1.3; the parameters of the ultrasonic step in step (3) of this embodiment are: ultrasonic power of 400 W, ultrasonic frequency of 40 kHz, ultrasonic temperature of 60° C., and ultrasonic time of 40 min.
[0054] The mass ratio of the gel, suspension, carbonyl iron powder and dimethyl silicone oil in step (4) of this embodiment is 3.05:4.5:50:89, and the viscosity of the dimethyl silicone oil in this embodiment is 1000 mPa·s; the parameters of the high-speed stirrer in step (4) of this embodiment are: stirring speed is 2000 rpm, and stirring time is 3 hours.
[0055] The degassing time in step (5) of this embodiment is 2 hours.
[0056] Example 3
[0057] A method for preparing a high temperature resistant wave absorbing composite rubber material, the preparation method of this embodiment comprises the following steps:
[0058] (1) Alumina fiber and KH550 are mixed, stirred in a high-speed stirrer to obtain surface-treated alumina fiber, and then ethyl orthosilicate, ethanol solution and deionized water are added, stirred at room temperature for 6 hours to form a sol, aged to obtain a gel;
[0059] (2) performing surface modification treatment on the filler to obtain a modified filler, and then mixing the modified filler with N-isopropyl-N'-phenyl-p-phenylenediamine and a softener and then ball milling to obtain a ball milling product;
[0060] (3) mixing the ball-milled product, acetone, and polyvinyl pyrrolidone, and performing ultrasonic dispersion to obtain a suspension;
[0061] (4) mixing the gel, the suspension, the carbonyl iron powder, and the dimethyl silicone oil, and stirring the mixture in a high-speed stirrer to obtain a mixed slurry;
[0062] (5) After the mixed slurry is degassed, it is filled to obtain a high temperature resistant and wave absorbing composite rubber material.
[0063] The mass ratio of alumina fiber and KH550 in step (1) of this embodiment is 4.83:1; the parameters of the high-speed stirrer in step (1) of this embodiment are: stirring speed is 1250rmp, stirring time is 15min; the mass ratio of surface-treated alumina fiber, tetraethyl orthosilicate, ethanol solution and deionized water in step (1) of this embodiment is 4.36:0.82:3.4:10; the mass concentration of the ethanol solution in this embodiment is 60wt%; the parameters of the aging step in step (1) of this embodiment are: aging temperature is 60°C, aging time is 18h.
[0064] The filler in step (2) of this embodiment is silicon dioxide; the mass ratio of the modified filler, N-isopropyl-N'-phenyl-p-phenylenediamine and the softener in step (2) of this embodiment is 5.5:0.74:1; the softener in this embodiment is cyclohexane oil; the parameters of the ball milling step in step (2) of this embodiment are: the ball milling speed is 500 rpm and the ball milling time is 3 hours.
[0065] The preparation method of the modified filler of this embodiment is:
[0066] The filler and methanol were mixed, and the ultrasonic temperature was set to 45°C. After ultrasonic treatment for 15 minutes, a suspension was obtained. γ-mercaptopropyltrimethoxysilane, styrene, and potassium persulfate were added, and the mixture was stirred at 50°C for 2 hours. Then, p-hydroxyanisole and diethylenetriamine were added, and 2wt% acetic acid solution was added dropwise. The mixture was stirred at 75°C for 2.5 hours. The mixture was filtered through a 200-mesh filter cloth. The obtained precipitate was washed with deionized water and dried to obtain a modified filler.
[0067] The mass ratio of the filler and methanol in this embodiment is 4.6:16; the mass ratio of the suspension, γ-mercaptopropyltrimethoxysilane, styrene and potassium persulfate in this embodiment is 6.23:0.92:1.05:0.05; the mass ratio of the mixture, p-hydroxyanisole, diethylenetriamine and 1-3wt% acetic acid solution in this embodiment is 5.25:0.65:0.77:0.1.
[0068] The mass ratio of the ball-milled product, acetone and polyvinyl pyrrolidone in step (3) of this embodiment is 5.3:8.5:1.1; the parameters of the ultrasonic step in step (3) of this embodiment are: ultrasonic power of 300 W, ultrasonic frequency of 35 kHz, ultrasonic temperature of 50° C., and ultrasonic time of 30 min.
[0069] The mass ratio of the gel, suspension, carbonyl iron powder and dimethyl silicone oil in step (4) of this embodiment is 2.7:3.95:35:67, and the viscosity of the dimethyl silicone oil in this embodiment is 1000 mPa·s; the parameters of the high-speed stirrer in step (4) of this embodiment are: stirring speed is 1750 rpm, and stirring time is 2 h.
[0070] The degassing time in step (5) of this embodiment is 1.5h.
[0071] Comparative Example 1
[0072] On the basis of Example 3, step (1) is changed to: alumina fiber, tetraethyl orthosilicate, ethanol solution and deionized water are mixed, stirred at room temperature for 6 hours to form a sol, aged to obtain a gel, and other conditions are consistent with Example 3.
[0073] Comparative Example 2
[0074] On the basis of Example 3, the preparation method of the modified filler is changed to: the filler and methanol are mixed, the ultrasonic temperature is set to 45°C, and a suspension is obtained after ultrasonication for 15 minutes. γ-mercaptopropyltrimethoxysilane, styrene, and potassium persulfate are added, and the mixture is stirred at 50°C for 2 hours to obtain a mixture, which is filtered through a 200-mesh filter cloth. The obtained precipitate is washed with deionized water and dried to obtain a modified filler. Other conditions are consistent with those in Example 3.
[0075] Comparative Example 3
[0076] On the basis of Example 3, the preparation method of the modified filler is changed to: the filler and methanol are mixed, the ultrasonic temperature is set to 45°C, and a suspension is obtained after ultrasonic treatment for 15 minutes. p-hydroxyanisole and diethylenetriamine are added, and a 2wt% acetic acid solution is added dropwise. The mixture is stirred at 75°C for 2.5 hours, filtered through a 200-mesh filter cloth, and the obtained precipitate is washed with deionized water and dried to obtain a modified filler. Other conditions are consistent with those in Example 3.
[0077] Comparative Example 4
[0078] On the basis of Example 3, the carbonyl iron powder was removed and replaced with an equal weight of dimethyl silicone oil, and other conditions were consistent with Example 3.
[0079] A mold of 180 mm × 180 mm × 1.5 mm was selected, and the absorbing composite rubber materials prepared in Examples 1-3 and Comparative Examples 1-4 were used as samples. They were placed at room temperature and 300° C. for 1 h, respectively, to test their absorbing performance. The reflection loss at the peak value is shown in Table 1.
[0080] Table 1 Absorption performance results
[0081]
[0082]
[0083] As shown in Table 1, the reflection loss of the wave-absorbing composite rubber materials prepared in Examples 1-3 of the present invention under high temperature conditions is better than that of the wave-absorbing composite rubber materials prepared in Comparative Examples 1-4. In Comparative Example 1, the treatment of KH550 is removed, so that the number of surface active groups decreases, the binding sites with subsequent materials are reduced, and the binding ability becomes smaller, which in turn affects the formation of the subsequent matrix skeleton and the embodiment of heat resistance; Comparative Examples 2 and 3 are both modified fillers, which are changed from double modification to single modification. First, the intermolecular force is reduced and the thermal stability is hindered. Second, it is impossible to form many tiny and uniform microscopic interfaces, and the electromagnetic wave loss is reduced, which leads to an increase in the overall reflection loss of the material and a weakening of the high temperature resistance; In Comparative Example 4, the use of carbonyl iron powder is removed, and the density and structural stability of the material in Example 3 cannot be achieved, and the high temperature resistance is weakened.
[0084] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a high temperature resistant wave absorbing composite rubber material, characterized in that: The preparation method comprises the following steps: (1) Alumina fiber and KH550 are mixed, stirred in a high-speed stirrer to obtain surface-treated alumina fiber, and then ethyl orthosilicate, ethanol solution and deionized water are added, stirred at room temperature for 4-8 hours to form a sol, aged, and obtained a gel; (2) performing surface modification treatment on the filler to obtain a modified filler, and then mixing the modified filler with N-isopropyl-N'-phenyl-p-phenylenediamine and a softener and then ball milling to obtain a ball milling product; (3) mixing the ball-milled product, acetone, and polyvinyl pyrrolidone, and performing ultrasonic dispersion to obtain a suspension; (4) mixing the gel, the suspension, the carbonyl iron powder, and the dimethyl silicone oil, and stirring the mixture in a high-speed stirrer to obtain a mixed slurry; (5) After the mixed slurry is degassed, it is filled to obtain a high temperature resistant and wave absorbing composite rubber material.
2. The method for preparing a high temperature resistant and wave absorbing composite rubber material according to claim 1, characterized in that: The mass ratio of alumina fiber and KH550 in step (1) is 4.21-5.45:0.8-1.2; the parameters of the high-speed stirrer in step (1) are: stirring speed is 1000-1500rmp, and stirring time is 10-20min; the mass ratio of surface-treated alumina fiber, tetraethyl orthosilicate, ethanol solution and deionized water in step (1) is 3.72-5:0.64-1:2.8-4:8-12; the mass concentration of the ethanol solution is 50-70wt%; the parameters of the aging step in step (1) are: aging temperature is 50-70°C, and aging time is 12-24h.
3. The method for preparing a high temperature resistant and wave absorbing composite rubber material according to claim 1, characterized in that: The filler in step (2) is selected from one or more of silicon dioxide, bentonite and diatomaceous earth; the mass ratio of the modified filler, N-isopropyl-N'-phenyl-p-phenylenediamine and the softener in step (2) is 4.7-6.3:0.6-0.88:0.8-1.2; the softener is selected from one of aromatic oil, cycloalkane oil and paraffin oil; the parameters of the ball milling step in step (2) are: the ball milling speed is 300-700 rpm, and the ball milling time is 2-4 hours.
4. The method for preparing a high temperature resistant and wave absorbing composite rubber material according to claim 3, characterized in that: The preparation method of the modified filler is: The filler and methanol are mixed, and the ultrasonic temperature is set to 35-55°C. After ultrasonic treatment for 10-20 minutes, a suspension is obtained, γ-mercaptopropyltrimethoxysilane, styrene, and potassium persulfate are added, and the mixture is stirred at 45-55°C for 1-3 hours to obtain a mixture, and then p-hydroxyanisole and diethylenetriamine are added, and 1-3wt% acetic acid solution is added dropwise, and the mixture is stirred at 70-80°C for 2-3 hours. The mixture is filtered through a 200-mesh filter cloth, and the obtained precipitate is washed with deionized water and dried to obtain a modified filler.
5. The method for preparing a high temperature resistant and wave absorbing composite rubber material according to claim 4, characterized in that: The mass ratio of the filler to methanol is 3.7-5.5:14-18; the mass ratio of the suspension, γ-mercaptopropyltrimethoxysilane, styrene and potassium persulfate is 5.45-7:0.72-1.12:0.9-1.2:0.03-0.07; the mass ratio of the mixture, p-hydroxyanisole, diethylenetriamine and 1-3wt% acetic acid solution is 4.5-6:0.52-0.78:0.61-0.93:0.05-0.
15.
6. The method for preparing a high temperature resistant and wave absorbing composite rubber material according to claim 1, characterized in that: The mass ratio of the ball-milled product, acetone and polyvinyl pyrrolidone in step (3) is 5.1-5.5:7-10:0.9-1.3; the parameters of the ultrasonic step in step (3) are: ultrasonic power of 200-400W, ultrasonic frequency of 30-40kHz, ultrasonic temperature of 40-60°C, and ultrasonic time of 20-40min.
7. The method for preparing a high temperature resistant and wave absorbing composite rubber material according to claim 1, characterized in that: The mass ratio of the gel, suspension, carbonyl iron powder and dimethyl silicone oil in step (4) is 2.35-3.05:3.4-4.5:20-50:45-89; the parameters of the high-speed stirrer in step (4) are: stirring speed is 1500-2000rmp, and stirring time is 1-3h.
8. The method for preparing a high temperature resistant and wave absorbing composite rubber material according to claim 1, characterized in that: The degassing time in step (5) is 1-2 hours.
